1983
DOI: 10.1111/j.1439-0485.1983.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

The Black Band Disease of Atlantic Reef Corals

Abstract: Abstract. The cyanophyte (Cyanobaclerium) that causes black band disease of Atlantic reef corals is described under the name Phormidium corallyticum, new species (family Oscillatoriaceae), and its generic placement is discussed from the standpoint of the GEITLERian (classical) and Drouet systems. Distinguishing characters include densely interwoven filaments that form a blackish mat and trichomes without significant cell wall constrictions, almost isodiametric cells (4.2 μm mean width, 4.0μm mean length) tape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(50 citation statements)
references
References 15 publications
(4 reference statements)
3
47
0
Order By: Relevance
“…Diseased lesions first appeared during the summer of 2001/2002, disappeared during the winter and then reappeared the next summer. Similar patterns have been reported in black band disease in the Caribbean and the Florida Keys (Rützler et al 1983, Edmunds 1991, Kuta & Richardson 1996, Bruckner & Bruckner 1997, yellow band disease on Acropora clathrata in the Arabian Gulf (Korrûbel 1998), white pox disease on A. palmata in the Florida Keys (Patterson et al 2002), white plague on corals in Puerto Rico (Bruckner & Bruckner 1997) and also in bacterial bleaching in Oculina patagonica (Kushmaro et al 1998). In a recent review of the ecology and aetiology of newly emerging marine diseases, Porter et al (2001) emphasise the repeated theme of a link between coral disease and temperature; although seasonality is not clear in all cases (Santavy et al 2001).…”
Section: In Situ Studiessupporting
confidence: 64%
“…Diseased lesions first appeared during the summer of 2001/2002, disappeared during the winter and then reappeared the next summer. Similar patterns have been reported in black band disease in the Caribbean and the Florida Keys (Rützler et al 1983, Edmunds 1991, Kuta & Richardson 1996, Bruckner & Bruckner 1997, yellow band disease on Acropora clathrata in the Arabian Gulf (Korrûbel 1998), white pox disease on A. palmata in the Florida Keys (Patterson et al 2002), white plague on corals in Puerto Rico (Bruckner & Bruckner 1997) and also in bacterial bleaching in Oculina patagonica (Kushmaro et al 1998). In a recent review of the ecology and aetiology of newly emerging marine diseases, Porter et al (2001) emphasise the repeated theme of a link between coral disease and temperature; although seasonality is not clear in all cases (Santavy et al 2001).…”
Section: In Situ Studiessupporting
confidence: 64%
“…More studies are necessary to determine the exact cause of high mortality in D. clivosa and moderate mortality of D. strigosa, and whether these results are reflected in the field. The observed differences in survival rates in the slowly increasing temperature experiment and SML thickness in the acidification experiment correspond with the patterns of differences in disease prevalence rates observed between D. labyrinthiformis and D. strigosa (Rützler and Santavy 1983;Edmunds 1991, Calnan et al 2008Jones et al 2012), and possibly contribute to the relative disease resistance of D. labyrinthiformis. Based upon the results of this study, it is clear that D. labyrinthiformis displays higher tolerance to increased temperatures than the other Diploria species.…”
Section: Comparison Between Speciessupporting
confidence: 72%
“…Rising temperatures have been associated with an increase in coral bleaching, with bleached corals being more susceptible to disease (Miller et al 2006;Bruno et al 2007;Muller et al 2008;Mydlarz et al 2009; labyrinthiformis showed no sign of disease (Calnan et al 2008). This trend has been observed throughout the wider Caribbean (Edmunds 1991), Belize, and Bermuda (Rützler and Santavy 1983). Despite its apparent relative resistance to disease, D. labyrinthiformis has been documented to bleach more quickly and intensely than D. strigosa on the reefs of the Caribbean (Villamizar et al 2008) and Bermuda (Cook et al 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Most reports on coral diseases (e.g. Antonius, 1981;Goldberg and Makemson, 1981;Rutzler et al 1983;Goldberg et al, 1984) do not include fungi among coral pathogens. It is assumed that their effect on the host is negligible, or that the fungi in corals are many saprophytes that exploit dead organic matter incorporated in coral skeletons by the coral or produced by endolithic algae and cyanobacteria (Kendrick et al, 1982).…”
Section: Discussionmentioning
confidence: 99%